Intracerebral and interhemispheric abscesses as a complication of acute purulent polysinusitis - A. A. Krivopalov; D. V. Leiko; A. Yu. Shcherbuk; Yu. A. Shcherbuk; P. A. Shamkina; A. V. Chufistova (Вестник хирургии имени И.И. Грекова)
A clinical case of an interdisciplinary approach to the treatment of a 20-year-old patient with acute purulent polysinusitis, complicated firstly by intracranial episubdural empyema, and then by intracerebral and interhemispheric abscesses, is presented. Despite the timely initiation of antibiotic therapy, the patient had intracranial purulent-inflammatory complica tions of acute purulent polysinusitis, which required the participation of a multidisciplinary team of medical specialists, the appointment of reserve antibiotics and repeated surgical interventions. The described clinical observation confirms that the influence on the course and outcome of the disease in patients with EnT-associated intracranial purulentinflammatory complications is exerted by: a multidisciplinary approach involving a neurosurgeon, otorhinolaryngologist, neurologist, radiologist, clinical pharmacologist, and anesthesiologist-resuscitator; early diagnosis, including computed tomography and/or magnetic resonance imaging of the brain and paranasal sinuses; early verification of the pathogen and determination of its sensitivity to antibiotics; timely etiotropic high-dose parenteral antibiotic therapy with drugs that penetrate the blood-brain barrier; radical rehabilitation of EnT-organs and intracranial foci of infection.